2012
DOI: 10.3733/ca.v066n03p102
|View full text |Cite
|
Sign up to set email alerts
|

Standards vary in studies using rainfall simulators to evaluate erosion

Abstract: Rainfall simulators are often employed to measure erosion rates, in order to estimate stream loading of sediment and nutrients in California foothill watersheds. The rainfall simulator enables the precise application of artificial rain with controlled drop sizes, intensity and duration. In addition to rain factors such as drop energy and intensity, several soil-and cover-related factors affect erosion rates. While computational models have evolved to quantify erosion based on field measurements taken by rainfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(27 citation statements)
references
References 41 publications
0
26
0
1
Order By: Relevance
“…Also, the effects of slope steepness and rain intensity on flow velocity intensified as slope gradient became steeper. It is obvious that at steeper slopes, the flow velocity and the resultant stream power and transport capacity of runoff increase so that more pre-detached materials can be transported by the raindrop-driven overland flow (Grismer 2012). In other words, due to higher flow velocities generated on steeper slopes, soil particles can be transported easier (Fu et al 2011).…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Also, the effects of slope steepness and rain intensity on flow velocity intensified as slope gradient became steeper. It is obvious that at steeper slopes, the flow velocity and the resultant stream power and transport capacity of runoff increase so that more pre-detached materials can be transported by the raindrop-driven overland flow (Grismer 2012). In other words, due to higher flow velocities generated on steeper slopes, soil particles can be transported easier (Fu et al 2011).…”
Section: Resultsmentioning
confidence: 98%
“…Defersha and Melesse (2012) found that rain intensity and slope gradient had significant influences on sediment concentration. Slope gradient is important as more soil particles are splashed down-slope than up-slope (Dunne et al 2010;Grismer 2012). In fact, slope gradient has a significant influence on the down-slope splash Comparison of sediment concentration between the studied soils showed that soil D 2mm exhibited higher values of sediment concentration than soil D 4.75mm (Fig.…”
Section: Sediment Concentrationmentioning
confidence: 90%
“…For example, Robichaud et al () using a blend of sizes of wood chips at three cover percentages (0, 50, and 70%) found that the largest erosion reduction was for a 70% cover. Gronier et al () reported that a 70% coverage of wood chips reduced soil loss by 98%. Yanosek et al () determined that two wood strand blends both reduced sediment loss by >70% for a range of coverages (30, 50, and 70%) for different soil types, slopes, and overland flow rates.…”
Section: Discussionmentioning
confidence: 99%
“…They found that all covered treatments reduced the runoff and sediment production when compared with a bare treatment subjected to rainfall only and rainfall plus concentrated flow. Gronier, Foltz, and Showers () evaluated the 30, 50, and 70% coverage of wood shred on sandy‐loam soil erosion under simulated rainfall intensity of 50 mm hr −1 . The results showed that the wood shred at 30, 50, and 70% coverage reduced sediment loss by 79, 92, and 98% as compared with bare plots.…”
Section: Introductionmentioning
confidence: 99%
“…Além disso, o impacto da gota de chuva proporciona compactação, que associada ao selamento, reduz a taxa de infiltração da água. Quando a intensidade da chuva passa a ser maior do que a taxa de infiltração, inicia-se o transporte das partículas desagregadas do solo pelo escoamento superficial (GRISMER, 2012).…”
Section: Fundamentação Teóricaunclassified